Suppression of the Cycloidal Spin Arrangement in BiFeO3 Caused by the Mechanically Induced Structural Distortion and Its Effect on Magnetism - Da Silva, Klebson Lucenildo; Trautwein, Rafael Santiago; Da Silva, Rodolfo Bezerra; Fabián, Martin; Čižmár, Erik; Holub, Mariia; Skurikhina, Olha; Harničárová, Marta; Girman, Vladimír; Menzel, Dirk; Becker, Klaus Dieter; Hahn, Horst; et al. (Frontiers in Materials, 2021)
Bismuth ferrite (BiFeO3) particles are prepared by a combined mechanochemical−thermal processing of a Bi2O3 + α-Fe2O3 mixture. Structural, magnetic, hyperfine, morphological and chemical properties of the as-prepared BiFeO3 are studied using X-ray diffraction (Rietveld refinement), 57Fe Mössbauer spectroscopy, SQUID magnetometry, electron microscopy and energy dispersive X-ray spectroscopy. It is revealed that the structure of the ferrite exhibits the long-range distortion (significantly tilted FeO6 octahedra) and the short-range disorder (deformed FeO6 octahedra). Consequently, these structural features result in the suppression of a space modulated cycloidal spin arrangement in the material. The latter manifests itself by the appearance of only single spectral component in the 57Fe Mössbauer spectrum of BiFeO3. The macroscopic magnetic behavior of the material is interpreted as a superposition of ferromagnetic and antiferromagnetic contributions with a large coercive field and remanent magnetization. Taking into account the average particle size of the as-prepared BiFeO3 particles (∼98 nm), exceeding the typical period length of cycloid (∼62 nm), both the suppression of the spiral spin structure in the material and its partly ferromagnetic behavior are attributed to the crystal lattice distortion caused by mechanical stress during the preparation procedure.